Twitter Sentiment Analysis on Halal Pharmaceutical - Syahdatul Maulida; Mohammad Mahbubi Ali (Ekonomi Islam Indonesia, 2023)
This study aims to analyze public sentiment towards halal pharmacy and halal pharmaceutical concepts. The data used is primary data sourced from the Twitter social media platform, focusing on the topic of halal pharmacy and halal pharmaceuticals. This data was subsequently processed using the Python Library known as VADER. The research findings indicate that, in the context of halal pharmacy, the public exhibits a positive sentiment tendency of 54.4%, followed by a neutral sentiment at 28.4%, and a negative sentiment of 17.2%. The prominent keywords that frequently appear include pharmacy, halal, pharmacies, best halal, Muslim rage, halal condom, and pharmacy product. Furthermore, it is noted that Auckland, New Zealand, emerges as the location with the highest number of tweets, amounting to 35. In contrast, concerning the concept of halal pharmaceuticals, there is a tendency towards a neutral sentiment at 51.7%, followed by a positive sentiment at 39.2%, and lastly, a negative sentiment at 9.0%. The research results also reveal that the dominant keywords appearing in tweets related to halal pharmaceuticals include halal, halal pharmaceutical, pharmaceutical industry, pharmaceutical company, pharmaceutical product, Malaysia, Brunei pharmaceutical, and global halal. It is noteworthy that the country with the highest number of tweets discussing halal pharmaceuticals is Malaysia, with a total of 127 tweets.